The prey of gods - Drayden, Nicky (Harper Voyager, an imprint of HarperCollinsPublishers, 2017)
In South Africa, the future looks promising. Personal robots are making life easier for the working class. The government is harnessing renewable energy to provide infrastructure for the poor. And in the bustling coastal town of Port Elizabeth, the economy is booming thanks to the genetic engineering industry which has found a welcome home there. Yes<U+2014>the days to come are looking very good for South Africans. That is, if they can survive the present challenges: A new hallucinogenic drug sweeping the country . . . An emerging AI uprising . . . And an ancient demigoddess hellbent on regaining her former status by preying on the blood and sweat (but mostly blood) of every human she encounters. It<U+2019>s up to a young Zulu girl powerful enough to destroy her entire township, a queer teen plagued with the ability to control minds, a pop diva with serious daddy issues, and a politician with even more serious mommy issues to band together to ensure there<U+2019>s a future left to worry about.